2018
DOI: 10.1002/hed.25425
|View full text |Cite
|
Sign up to set email alerts
|

Posttreatment surveillance PET/CT for HPV‐associated oropharyngeal cancer

Abstract: Background Surveillance positron emission tomography‐computed tomography (PET/CT) is commonly used for treatment assessment of radiation therapy in head and neck cancer. However, human papillomavirus‐associated oropharyngeal squamous cell carcinoma (HPV+OPSCC) patients represent a unique subpopulation, for which the utility of surveillance PET/CT has not been well studied. Methods In this retrospective chart review comprising 233 HPV+OPSCC patients, we evaluated surveillance PET/CT for diagnostic accuracy, dow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 30 publications
0
26
0
Order By: Relevance
“…In the most recent study investigating the use of PET/CTs for surveillance of HPV associated OPSCCs (i.e. when there was no clinical suspicion of disease recurrence), the positive predictive value was only 13.4% [ 53 ]. However, evidence suggests that circulating biomarkers have the potential for detecting early recurrences.…”
Section: Discussionmentioning
confidence: 99%
“…In the most recent study investigating the use of PET/CTs for surveillance of HPV associated OPSCCs (i.e. when there was no clinical suspicion of disease recurrence), the positive predictive value was only 13.4% [ 53 ]. However, evidence suggests that circulating biomarkers have the potential for detecting early recurrences.…”
Section: Discussionmentioning
confidence: 99%
“…Among the key prognostic markers for survival, epidermal growth factor receptor (EGFR), cyclin D1(CCND1), ERCC1, p16, human papillomavirus (HPV), and B‐cell lymphoma‐extra large (Bcl‐xL)/Bcl‐2, as well as the amplification of genes including EMS1 , FGFR1 , and CCND1 have demonstrated some evidence in clinical trials. Others are slower to advance in clinical development because of unconvincing data and few published studies; for example, acetylcholinesterase(AchE), SNPs of specific genes, glutathione S‐transferase (GST), CD44, amplification of specific genes, hypoxic markers, KLK‐6, and MDA‐7/IL‐24; although, this does not preclude them from future investigations and clinical utility.…”
Section: Biomarkers In Hnscc Tumor Tissuesmentioning
confidence: 99%
“…For purposes of negative predictive value (NPV) and positive predictive value (PPV) all studies reported a discrete negative and positive group. However, Corpman et al 19 combined positive and equivocal groups in their analysis and only 3 studies (Rulach et al, 20 Vainshtein et al, 21 and Wang et al 22 ) analyzed an equivocal group separately. Therefore, PET/CT treatment response data was pooled by a negative, positive, equivocal, or equivocal/positive designation depending on study protocol and reporting criteria used (Table 1).…”
Section: Methodsmentioning
confidence: 99%